Financial Distress and Governance Structure: An Empirical Study of Property and Real Estate Companies in Indonesia - Jannah, Vika Miftahul; Edward, Yurnal; Fristy, Anne Monika; Antoni.R, Stevanus (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of the audit committee and the board of commissioners on financial distress in property and real estate companies listed on the Indonesia Stock Exchange for the 2023–2024 period. The research population consisted of 94 companies, with a final sample of 61 companies (122 observations) selected through purposive sampling. Data analysis was performed using multiple linear regression with SPSS software. The results show that the audit committee has no significant effect on financial distress, indicating that its presence tends to serve as a regulatory formality rather than an effective monitoring mechanism. In contrast, the board of commissioners has a significant effect on financial distress, suggesting that effective supervisory roles can reduce the likelihood of financial difficulties. These findings reinforce agency theory, emphasizing that strong corporate governance mechanisms play a crucial role in mitigating agency conflicts and maintaining financial stability. The study implies that companies should strengthen the effectiveness of their boards of commissioners and that regulators need to ensure the substantive role of audit committees in corporate governance practices.